Medieval English manuscripts and literary forms - Brantley, Jessica (Material texts., 2022)
"In Medieval English Manuscripts and Literary Forms, Jessica Brantley offers an innovative introduction to manuscript culture that uses the artifacts themselves to open some of the most vital theoretical questions in medieval literary studies. With nearly 200 illustrations, many of them in color, the book offers both a broad survey of the physical forms and cultural histories of manuscripts and a dozen case studies of particularly significant literary witnesses, including the Beowulf manuscript, the St. Albans Psalter, the Ellesmere manuscript of the Canterbury Tales, and The Book of Margery Kempe. Practical discussions of parchment, scripts, decoration, illustration, and bindings mix with consideration of such conceptual categories as ownership, authorship, language, miscellaneity, geography, writing, editing, mediation, illustration, and performance--as well as of the status of the literary itself. Each case study includes an essay orienting the reader to particularly productive categories of analysis and a selected bibliography for further research. Because a high-quality digital surrogate exists for each of the selected manuscripts, fully and freely available online, readers can gain access to the artifacts in their entirety, enabling further individual exploration and facilitating the book's classroom use. Medieval English Manuscripts and Literary Forms aims to inspire a broad group of readers with some of the excitement of literary manuscript studies in the twenty-first century. The interpretative frameworks surrounding each object will assist everyone in thinking through the implications of manuscript culture more generally, not only for the deeper study of the literature of the Middle Ages, but also for a better understanding of book cultures of any era, including our own."--